Narratives as Meaningful Learning Experiences (Global Journal of Human-Social Science, 2014)
This work focuses on exploring the use of narratives as a process of communication and meaning making, thereby reviewing different contributions by different research lines. The questioning from narratives is a learning experience that is shaping a common space, interacting with learning as a process, and the beginning of critical thinking as a product. Since the beginning of the process of access to reading, we can stimulate the ability to question and to reflect that, over time, will become an essential foundation for reading for pleasure. We build our common meanings based on the knowledge of reality in terms of the cultural context to which we belong. Children need to read or listen to stories read to find information on any area of knowledge.
Keywords: stories; discussion; elaboration of meaning; constructivism; cultural psychology